Periculosidade: uma (insustentável) qualidade atribuída - Arruda, Ana Luiza Gardiman (2018)
Dangerousness is a controversial issue in criminal law by presenting two bases that distinctly affect the system. In matters of constraint of safety measures relating to non-imputable violators, the dangerousness takes the role of the psychiatry concept; when it is shown in the personality analysis of the imputable violator or in reprisals during the penalty execution, it takes shape of interdisciplinary, covering social issues inferences. The real use of dangerousness is questioned as a criterion for the criminal penalty, taking into account its incompability with legal category of culpability; and the relation between dangerousness, cruelty and enemy election. The starting point of analysis is the historical context of the emergence of the segregation idea of dangerous individuals, with the scope of demonstrating its interference in a construction that became theory, based on the distortion of the philosophy of Hegel. The study of criminal positivism, the clinical criminology and neuroscience will demonstrate that, for different approaches, the same is intended: penal law of an author based on the individual’s dangerousness. The study will then, analyze the dangerous individual according to Foucault’s studies. According to this, important themes will be proposed such as the relation between medicine and law, leading in the study of personality; the criminological exam and its controversial application nowadays; the safety measures and the proposals for psychiatric reform. Considering the role of social control, the study will analyze the dangerousness as a stigma and as an argument of exclusion, fact that will show that it is an unacceptable attributed quality. Still in this sense, the study will undergo the criminal law of the enemy and its influence on the current criminal law sciences searching for a philosophical answer to the social need of classifying people as dangerous. The study will be done using Nietzsche’s theory. Finally, it will treat the incompatibility between dangerousness and culpability considering important issues such as the differences between the criminal law of the author and criminal law of the fact; as well as the culpability as a limit to law enforcement. With all this, the aim is to show the existence of dangerousness in every individuals and, at the same time, its incompatibility with the penal system of culpability